Interactive gaming computer technologies in the study of ecology (Pedagogy of Higher and Secondary Education, 2012)
Grishchenko S. M. Interactive gaming computer technologies in the study of ecology.The article deals with the content and structure of the interactive gaming computer technology in the study of ecology.
Keywords: game; game technology; ecology